Inversion du sujet dans la collection de contes de fées de Charles Perrault - Balqis Fathian Azra; Neli Purwani (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
In French, the position of words in a sentence determines its meaning. In some cases, the position of words can be interchanged. For example, in the construction of an interrogative sentence that presents the first verb followed by the subject, this construction places the subject to the right of the verb. This construction is called inversion. This study aims to discover and describe subject inversion in Charles Perrault's fairy tales. This research uses a qualitative approach. The result of this research is 37 instances of subject inversion from three of Charles Perrault's fairy tales, as presented in the book Contes de ma mère l'Oye. Of the 37 data points obtained, 21 are simple inversion data points and 16 are final inversion data points. The data obtained include (1) subject inversion in subordinate clauses of complex sentences, with up to 7 data points (simple inversion totaling 5 data points and final inversion totaling 2 data points), (2) subject inversion in simple sentences totaling 30 instances (simple inversion totaling 16 instances and final inversion totaling 14 instances), (3) subject inversion in declarative sentences totaling 24 instances (simple inversion totaling 11 instances and final inversion totaling 13 instances), (4) subject inversion in interrogative sentences totals 7 data points (simple inversion totals 6 data points and final inversion totals 1 data point), (5) subject inversion in exclamatory sentences totals 2 data points, namely simple inversion.